2009
DOI: 10.1182/asheducation-2009.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for non-sickling hemoglobinopathies

Abstract: The hemoglobinopathies encompass a heterogeneous group of disorders associated with mutations in both the alpha-globin and beta-globin genes. Non-sickling disorders are found primarily in individuals of Mediterranean, Asian and Southeast Asian ancestry. With rapid growth in the Asian and Hispanic segments of the US population, the geographic distribution of hemoglobinopathies is expected to become significantly different from what it is today. The epidemiologic changes in the prevalence of non-sickling hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
2
34
1
1
Order By: Relevance
“…Once rare in North America, it is becoming a major public health problem. There has been a 2000% increase in Asian and other at-risk populations immigrating to the United States in the last three decades (Hoppe 2009). This has resulted in California establishing universal newborn screening for a-thalassemia, and consideration of a national a-thalassemia newborn screening policy (Benz 2011).…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Once rare in North America, it is becoming a major public health problem. There has been a 2000% increase in Asian and other at-risk populations immigrating to the United States in the last three decades (Hoppe 2009). This has resulted in California establishing universal newborn screening for a-thalassemia, and consideration of a national a-thalassemia newborn screening policy (Benz 2011).…”
Section: Epidemiologymentioning
confidence: 99%
“…Most of them are named by the place of origin of their discovery. The most common form is the Southeast Asian deletion ( -SEA ) (Chui and Waye 1998;Hoppe 2009). This deletion involves both a genes but not the embryonic globin genes (Chui and Waye 1998).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Only limited race-specific disorder profiles have been reported elsewhere. Previous research has examined the relationship between ethnicity and a single genetic disorder, including the prevalence of a mutation or disorder within a specific ethnic group, [4][5][6][7][8] within several ethnic groups in a region, [9][10][11][12][13][14][15][16][17] or by geographic region only. 18,19 No studies have published the disorder prevalence rates by specific racial/ethnicity groups in a large US population.…”
Section: Introductionmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC), however, is the traditional common technique currently employed in the majority of laboratories. HPLC is effective in neonatal screening for hemoglobinopathies [17][18][19][20]. There were studies comparing diagnostic performance between the Sebia Capillarys 2 system and HPLC, and found that both techniques were suitable for the identification and quantification of both common and unusual hemoglobin variants, producing comparable results [21,22].…”
Section: Discussionmentioning
confidence: 99%